Energy optimization analysis of archetype public buildings – Results from SHERPA European Project - de Rubeis Tullio (EDP Sciences, 2021)
In this paper, the main results obtained for the identification of energy efficiency measures (EEMs) in archetype public buildings selected by the Abruzzo Region within the European Project SHERPA (SHared knowledge for Energy Renovation in buildings by Public Administration), a three-year project involving 12 partners from the Mediterranean area, are presented.The analysis presented in this work was carried out on 12 public buildings, with different intended use, located in the four provinces of the Abruzzo Region characterized by different climate conditions. For each building, a complex work of documents acquisition has been carried out together with the regional coordinators of the Project. These documents have allowed the energy assessment of the selected buildings in their current condition. The second phase of the study has instead focused on the effects resulting from the application of EEMs on both passive and active components, in terms of energy savings and greenhouse gas (GHG) emissions reduction. The results obtained have permitted to compare different public buildings, in different climate conditions, identifying EEMs and achievable results that may be useful to policy makers for the identification of appropriate energy optimization strategies and financial instruments for their implementation.